2007
DOI: 10.1002/hep.21691
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofPFTAIREprotein kinase 1, a novel cell division cycle-2 related gene, in the motile phenotype of hepatocellular carcinoma cells

Abstract: Metastasis is a major cause of cancer morbidity and mortality in individuals with hepatocellular carcinoma (HCC), yet little is known about the underlying molecular basis. Using genetic information derived from chromosome-based comparative genomic hybridization, we have reported previously on regional chromosome 7q21-q22 gains in close association with HCC progression. In this study, we undertook cDNA microarray-based comparative genomic hybridization, to examine the 7q21-q22 region for the involved gene(s) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
(30 reference statements)
6
40
0
Order By: Relevance
“…As PFTK1 is a novel member of the Cdc2 family, few studies have been performed to characterize its physiological function or biological importance. We defined a role for PFTK1 as a regulatory factor in the control of HCC cell migration (Pang et al, 2007). Although it has been long recognized that Cdc2 proteins have vital roles in the control of cell cycle transitions in eukaryotic cells (Kirschner, 1992;Pines, 1992;Solomon, 1993) and would be suspected to have minimal influence on cell migrations, in line with our findings, an earlier study also showed that upregulation of Cdc2 could enhance cell migration through activating cyclin B2 and caldesmon in promoting actin contractility (Manes et al, 2003).…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…As PFTK1 is a novel member of the Cdc2 family, few studies have been performed to characterize its physiological function or biological importance. We defined a role for PFTK1 as a regulatory factor in the control of HCC cell migration (Pang et al, 2007). Although it has been long recognized that Cdc2 proteins have vital roles in the control of cell cycle transitions in eukaryotic cells (Kirschner, 1992;Pines, 1992;Solomon, 1993) and would be suspected to have minimal influence on cell migrations, in line with our findings, an earlier study also showed that upregulation of Cdc2 could enhance cell migration through activating cyclin B2 and caldesmon in promoting actin contractility (Manes et al, 2003).…”
Section: Introductionsupporting
confidence: 82%
“…7q21-q22 of HCC. Our earlier investigations by ectopic expression and gene knockdown experiments confirmed an important role for PFTK1 in the cellular invasiveness and motility of HCC cells (Pang et al, 2007). Nevertheless, the biological basis that underlies the action of PFTK1 in conferring cell migratory properties in HCC remains unknown.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations